2022
DOI: 10.1177/0192513x221113853
|View full text |Cite
|
Sign up to set email alerts
|

Do Migrant Parents’ Income or Relationships With Their Left-Behind Children Compensate for Their Physical Absence?

Abstract: Parental migration from rural to cities in China is causing millions of children to be left behind or to live without parental care, support, and guidance, which violates the Convention on the Rights of the Child. This national phenomenon has consequences for the household registration system, known as the hukou system, which is meant to restrain internal migration. These consequences may result in economic and social imbalances. However, a noticeable number of children have been completely or partially left b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The current study revealed that the pattern of LBCs’ social adjustment was neither positive nor negative as mounting evidence indicated that the disadvantaged children were prone to a broad array of adverse social outcomes; nevertheless, they developed the resilience to respond to adversity and adjust to their environment [ 34 ]. Effective parent–child interaction after being left behind also had a compensation effect on LBCs’ well adjustment [ 35 ]. In addition, though we found that LBC experienced negative emotional states and poor academic performances, they could still balance the needs of the school, family, and society.…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed that the pattern of LBCs’ social adjustment was neither positive nor negative as mounting evidence indicated that the disadvantaged children were prone to a broad array of adverse social outcomes; nevertheless, they developed the resilience to respond to adversity and adjust to their environment [ 34 ]. Effective parent–child interaction after being left behind also had a compensation effect on LBCs’ well adjustment [ 35 ]. In addition, though we found that LBC experienced negative emotional states and poor academic performances, they could still balance the needs of the school, family, and society.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the rural parents’ migration, the size of remittance is an essential matter for left-behind children and their migrant parents. Most participants confirmed that their parents’ motives for moving to an urban locality were to meet their family’s obligations [ 49 ]. The psychological state of LBC is further subdivided into LBC’s view of COVID and LBC’s parents during COVID.…”
Section: Methodsmentioning
confidence: 98%
“…In addition, migrant workers in China face particularly severe problems and challenges under the pandemic restrictions, and their unstable employment, income, and life security circumstances have worsened [ 24 ]. Most migrant parents became stuck in their home villages after returning for Chinese spring festival celebrations, and another group became trapped in their workplaces, and could not return to their homes [ 16 , 24 , 49 , 50 ]. A two-province survey study by Wang et al assessed LBC; rural children who lived with both parents showed lower loneliness during the COVID-19 outbreak [ 23 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations